Evaluation of Metabolic Dysfunction-Associated Steatotic Liver Disease in Patients with Type 2 Diabetes Mellitus - Hilmi Erdem Sümbül; Tayyibe Saler; Ahmet Gazi Mustan; Cahit Dincer; İrfan Alişan; Bercem Berent Kaya; Mehmet Can Erişen; Bektaş Işık; Begüm Şeyda Avci; Fatih Necip Arici; Dilan Damla Ozturk; Erdinc Gulumsek; et al. (Sakarya Tıp Dergisi)
Aim: Diabetes mellitus (DM) is associated with the development and progression of metabolic dysfunction-associated steatotic liver disease (MASLD). In our study, we aimed to evaluate the findings of MASLD and fibrosis according to liver ultrasound (USG) imaging, FIB-4 score and fibroscan findings in patients with type 2 DM followed in our internal medicine clinic.Methods: In our retrospective and cross-sectional study, 1282 patients diagnosed with type 2 DM whose anamnesis and previous examinations did not constitute an obstacle for inclusion in the study were included. The abdominal USG imaging of the patients were analysed from the system and the FIB-4 score was calculated. Liver stiffness (LS) measurements were performed with FibroScan® Mini 430 device (Echosens, France).Results: USG imaging was performed in 474 (36.9%) of 1282 patients and MASLD was diagnosed in 341 (71.9%) of these patients. FIB-4 score> was 1.3 in 45 of 341 patients diagnosed with MASLD. Fibroscan imaging was performed in 231 of 341 patients with MASLD. In 52 (22.5%) of 231 patients, LS measurements> were 8 kPaConclusion: We recommend early screening of MASLD, which is associated with advanced fibrosis and increased cardiovascular mortality and morbidity in patients with DM, with liver USG, measurement of FIB-4 score and evaluation of LS with fibroscan in centres where possible.